Persepsi Masyarakat Terhadap Eksistensi Komunitas sub-culture PUNK Ditinjau Dari Aspek Sosial (Studi Kasus Komunitas Punk di Kecamatan Cisoka) - Pambudi, Gigih Adhi; Hayat, Nurul; Widiansyah, Subhan (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
The punk sub-culture community is a community that is dominated by teenagers and their appearance style is different from society in general, such as the way they dress and also their lifestyle, political views. This difference occurs because of conflict as a community that is considered a minority against certain values. from the majority culture, which is considered to be contrary to the life principles of members of sub-cultural communities, especially the Punk sub-culture. This research uses qualitative methods, and the research location is in Cisoka sub-district, Tangerang Banten Regency.